Reproductive effort influences intra‐seasonal variation in parasite‐specific antibody responses in wild Soay sheep. (25th April 2019) - Hayward, Adam D.; Pilkington, Jill G.; Wilson, Kenneth; McNeilly, Tom N.; Watt, Kathryn A.
Abstract: A trade‐off between reproduction and immune function has been suggested to potentially underpin between‐individual and genetic variation in reproductive strategy, immunity and life span, with potential consequences for host and parasite dynamics. Previous studies in wild animal populations have shown that experimentally induced or natural variation in reproductive effort is negatively associated with general immune markers. Few studies, however, have tackled this question by measuring specific immune responses against prevalent pathogens, and only rarely has variation in immune measures been linked to parasite burden, making it impossible to draw conclusions about the functional relevance of covariation between reproductive effort and immune markers. We collected faecal samples in a longitudinal manner from wild female Soay sheep across late pregnancy and early lactation and measured gastrointestinal nematode faecal egg count (FEC) and worm‐specific antibody responses. Faecal egg count was highly repeatable, with c . 80% of variation due to between‐individual differences, while three isotypes of worm‐specific and total antibodies had moderate repeatability (range: 11%–43%). Females making a greater reproductive effort (those that reproduced, and especially those with heavier litters) showed a more rapid increase in FEC across the season, while non‐reproducing females and those producing lighter litters experienced lower FEC and had higher antibody levels. Associations between antibodies and FEC were complex: worm‐specific immunoglobulin (Ig) G was negatively associated with FEC, while total IgM was positively associated, emphasizing the importance of measuring both immune markers and parasite burden in ecological studies. Our results support the predicted trade‐off between reproductive effort and parasite‐specific immunity: high reproductive effort can limit the ability of individuals to defend themselves against prevalent parasites, with potential downstream consequences for fitness and parasite transmission. A plain language summary is available for this article. Abstract : Plain Language Summary